Penguatan Kepedulian Sosial Warga Belajar melalui Program Takjil dan Buka Puasa Bersama di PKBM Panrita Kota Parepare - Dithamaya Cahyaniengsih Pratiwy; A. Hasdiansyah; Ihwan Ridwan; Salmia Salama (Prodi PGSD Unsultra, 2026)
This community service activity aimed to strengthen the social awareness of learners at PKBM Panrita, Parepare City, through the Takjil Sharing and Collective Iftar Program. The activity was initiated based on the need to develop learning experiences that extend beyond classroom boundaries and encourage learners to engage directly with the community. This program was designed as an experiential learning activity that enables learners to participate in social practices, build meaningful interactions, and develop values of empathy, solidarity, and social responsibility. The implementation method applied a participatory approach involving learners, tutors, and PKBM managers in all stages of the program. The activity stages included program planning, task distribution, preparation of takjil packages, packaging activities, distribution to the community, collective iftar, and reflection sessions. Data were collected through participatory observation, activity documentation, process records, and informal reflections from participants. The results showed that the Takjil Sharing and Collective Iftar Program positively contributed to the development of learners’ social attitudes. The activity strengthened empathy, teamwork skills, communication abilities, responsibility, confidence in social interaction, and a sense of belonging toward PKBM as a community learning institution. Furthermore, the program demonstrated that PKBM can serve as a community-based educational space that connects equivalency education, character development, and social empowerment. Supporting factors included learners’ enthusiasm, support from tutors and managers, the Ramadan atmosphere, and the culture of mutual cooperation. The challenges encountered were limited funding, short preparation time, and insufficient reflective documentation. This program is recommended to become an annual social initiative of PKBM supported by implementation guidelines, achievement indicators, structured reflection activities, and broader involvement of alumni, local partners, and surrounding communities.